Fat, Stressed, and Sick: MSG, Processed Food, and America's Health Crisis - Reid, Katherine; Price, Barbara (Rowman & Littlefield Publishers, 2023)
Presents the scientific evidence that glutamate—aka MSG—in processed food contributes to a suite of preventable inflammatory diseases. Fat, Stressed, and Sick makes the case that processed food compromises health not just because of added sugar, salt, and fat, but also because these foods contain significant amounts of glutamate—aka MSG. MSG makes food deliciously addicting. What was not well-known until described here is that most of the MSG in processed food is created during food manufacturing. As the authors show, food processing of protein alone adds 10 grams or more a day of MSG to the average American diet—a statistic that may surprise you. The book details the research linking dietary glutamate to a suite of inflammatory diseases: obesity, diabetes, autism, addiction, depression, and cancer, to name a few. Understanding the role of MSG in disease became the quest of author and biochemist Katherine Reid when she learned that her young daughter’s autism symptoms were associated with inflammation of the brain. Reid made the connection between inflammation and glutamate in the diet—a connection amply supported by other studies. A deep dive into food manufacturing patents and FDA regulations revealed that, in addition to industry practices that create MSG during food processing, MSG is also found in ingredients labeled “hydrolyzed protein,” “yeast extract,” and even “natural flavors,” misleading labels that disguise a food’s true MSG content. In what became an experiment in her home kitchen, Reid examined every ingredient on every food label, removing all items with MSG and replacing them with whole foods. The results were swift and undeniable. Reid’s discovery that what one ate mattered was the start of a program of food-based solutions to chronic inflammatory illnesses, through which now, a decade later, she has helped thousands of people. The idea that large amounts glutamate in the diet jeopardizes health is supported by decades of research, despite efforts by the glutamate industry to discredit the scientific evidence that MSG poses a risk. Some would have you believe the science is settled. It is not. This book explains the science behind why we crave the MSG in processed food, why it is hidden, how it is making us sick, and what we can do about it.